A Fourth Grade Student’s Exploration of Variable Notation Through a Function Representation Task. - Sawrey, Katharine B. (Tufts Archival Research Center, 2017)
A qualifying paper submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Education. Abstract: In this paper, I examine a fourth grade student’s discourse and work with variable notation in the context of a function representation task. In spite of being unfamiliar with variable notation previous to this task, the student seemed to gain some awareness of the symbolizing significance of variable notation. I argue that the student’s statements and conjectures about the equations were acts of sense-making mediated by other function representations and by discourse during the interview. The student’s achievements with the task provide evidence that upper elementary students can draw on personal resources to make sense of algebraic equations with variable notation.